3D Finite Element Modelling of Sheet Pile Wall Excavation: A Case study in Bangkok - Chhunla Chheng; Suched Likitlersuang (IPTEK Journal of Proceedings Series, 2017)
Sheet pile wall has been used extensively as a soil retaining structure during the excavation process in soft ground. Meanwhile, finite element method (FEM) has been widely used as a numerical tool to predict wall movements due to soil excavation. In FEM, many factors including soil parameters, structures’ parameters and construction stages simulation influence the analysis results. This paper presents a modelling of sheet pile wall at deep excavation using 3D FEM. The study focuses on the structures’ stiffness modelling and the stages of construction simulation. The hardening soil model and its parameters adopted from previous study was employed in the analysis. To validate the model, an excavation site located in the center of Bangkok was selected to model. PLAXIS 3D – a commercial software for solving finite element problem was employed in this study. In overall, the results of wall movements from 3D FEM agree well with the instrumented data confirming that the modelling could reflect the real behavior of sheet pile walls at deep excavation in soft soils in Bangkok